Kamal Hassan’s vision remembered: a tribute through the eyes of Prof. Mumtaz Ali - Abdul Razak, Mohd Abbas (Department of Communication, KIRKHS, IIUM, 2025)
On Friday, 17th October 2025, an intellectual discourse was organized to honour the late Prof. Ulung Tan Sri Mohd Kamal Hassan. The event was hosted by the Office of the Coordinator of Islamization of Knowledge, AHAS KIRKHS, IIUM. The topic for that morning was “The Essence and Relevance of the Views of Kamal Hassan.” The presenter was none other than the distinguished Prof. Mohd Mumtaz Ali from the Department of Usul al-Din and Comparative Religion. As a speaker, Prof. Mumtaz Ali has not only deeply immersed himself in the works of Kamal Hassan and interacted with him at the intellectual level, but he can also be regarded as one who had the privilege of dining and engaging with him in many other capacities. Dr. Saheed Abdullahi Busari, a specialist in Islamic Jurisprudence, was entrusted by the Kulliyyah to serve as the chairperson for this intellectual banquet. The sharing sessions by the main speaker and other participants truly provided a feast of ideas and food for thought. The Dean of the Kulliyyah, Prof. Dr. Hafiz Zakariya, who graced the occasion as the special guest, mentioned in his opening remarks that Prof. Mumtaz is a scholar worth listening to, as he is among those who know Prof. Kamal Hassan inside out.